THEORETICAL ANALYSIS OF TYPES AND FORMS OF CORRUPTION IN THE PUBLIC SERVICE (Academia Science Repository, 2023)
The article examines various types and forms of that are widespread in the modern world. The author proposes various approaches to the classification of corruption depending on the subjects of corruption, the scale of territorial coverage and the degree of participation of officials.